Use of Prostaglandin E(2) in the Management of Missed Abortion, Missed Labour, and Hydatidiform Mole - Karim, S. M. M. (1970)
Treatment of six cases of missed abortion and one case of hydatidiform mole with intravenous infusion of prostaglandin E(2) resulted in complete abortion in all cases. Of 15 patients with missed labour, 14 were delivered successfully with similar treatment. The technique appears to be a safe, reliable, and rapid method of managing missed abortion, missed labour, and hydatidiform mole.